Is there a rational bubble in bist 100 and sector indices? - Ayşegül Kirkpinar; Elif Erer; Deniz Erer (Financial Studies, 2019)
Global financial crises, which can stem from the bubbles in asset prices and which have been observed especially in the United States and Europe, have demonstrated once again how important the determination of bubbles is. The bubbles in question in financial markets are referred as excessive increase in asset prices. When considering the close relationship of rational bubbles with financial crises, the analysis and detection of them become even more important for investors, portfolio managers and market regulators.For this purpose, the aim of this study is to examine the existence of rational bubbles in BorsaIstanbul 100 Index (BIST 100) and some sector indices for the period of 1990-2015. For this, right-tailed unit root test, Sup Augmented Dickey-Fuller test and Generalized Sup Augmented Dickey-Fuller test have been used. As a result of the analyses, it has been observed that no rational bubbles existed in BIST 100 and the mentioned sector indices. Our findings may provide policy makers and both domestic and international investors in order to makeappropriatedecision and thus, to take a position in the markets.
Keywords: G10; G17; 330; bubbles; BIST 100; sector indices; SADF; GSADF